THE IMPORTANCE OF USING DIGITAL PEDAGOGY IN HIGHER EDUCATIONAL ENVIRONMENT - Akhmedov Abdulaziz Mashrabovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the role of digital pedagogy in ensuring the quality of higher education and its important aspects. Factors that positively affect the quality and effectiveness of education are analyzed. The analysis of specific aspects of the application of traditional and digital pedagogy in the learning process is described.